Narsisme Dalam Pelaporan Corporate Social Responsibility: Analisis Semiotik Atas Sustainability Reporting PT. Kaltim Prima Coal Dan PT. Perkebunan Nusantara XIII (Persero) - Diajeng Ade Sakina; Nining Ika Wahyuni; Imam Mas'ud (UPT Penerbitan Universitas Jember, 2014)
Sustainability reporting is one of accountability form of the company in the disclosure of organizational performance that includes economic reports, social, and enviromental. The existence of narrative text in the sustainability reporting gives the company an opportunity to affect the stakeholders by the way to manipulate sentences are used. The purpose of this research was to analize the structure of sustainability reporting and to investigate whether there was a use of language narcisism on the report or not . This research was conducted in qualitative research methods by using semiotic ananlysis. The data analized were sustainability reporting on one of mining and plantation company. The result of this research showed that the structure of sustainability reporting on both companies (PT. Katim Prima Coal dan PT. Perkebunan Nusantara XIII) had a lot similarities although both of them have Â different characetrisitics. In addition, this research also showed that there was language narcicism that can be classified as the comapnyâ€™s efforts in forming positive images, avoiding negative images and obtaining legitimation from the stakeholders.